Two new cavernicolous species of Entomobryidae (Collembola) from Turkmenistan, Central Asia - Mayvan, Mahmood Mehrafrooz; Lips, Josiane; Kováč, Ľubomír (Zootaxa, 2025)
Descriptions of two new cavernicolous collembolans of the family Entomobryidae Womersley, 1934 from Turkmenistan resulted from speleological expeditions organized by the association Karstology & Researchs in Central Asia (KRAC) and sponsored by the Commission for International Relations and Expeditions (CREI) of the French Speleology Federation to caves and mines in the Koytendag Mountains in 2023–2024. Two new species, Entomobryoides gruati sp. nov. and Drepanura koytendagi sp. nov. are described as the first Collembola discovered from subterranean ecosystems of Turkmenistan, Central Asia. Tables summarizing the diagnostic characters of world species of Entomobryoides Maynard, 1951 and Drepanura Schött, 1891 are provided. Both new species are associated with subterranean habitats in dark cave zones. The discovery of two cave entomobryids highlight the high biodiversity potential of Turkmenistan’s cave ecosystems and suggest that vast majority of undescribed species are yet to be found. Given the minimal exploration of this region, a further biospeleological effort is essential to reveal diversity, distribution and endemicity of subterranean fauna in Central Asia.